2019
DOI: 10.1183/13993003.01409-2019
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterisation of pulmonary subsolid nodules: mutational landscape and radiological features

Abstract: BackgroundLung adenocarcinomas (LUADs) that display radiologically as subsolid nodules (SSNs) exhibit more indolent biological behaviour than solid LUADs. SSNs, commonly encompassing pre-invasive and invasive yet early-stage adenocarcinomas, can be categorised as pure ground-glass nodules and part-solid nodules. The genomic characteristics of SSNs remain poorly understood.MethodsWe subjected 154 SSN samples from 120 treatment-naïve Chinese patients to whole-exome sequencing. Clinical parameters and radiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 27 publications
8
50
0
Order By: Relevance
“…1 ). The result was similar to the previous reports in which RBM10 was found with a high mutation rate (16%) in radiological subsolid nodules 25 , and a high mutation rate (21%) in preinvasive and early-stage lung adenocarcinomas 26 . In addition, several oncogenes (such as EGFR , SPTA , and RB1 ) had different mutations in the same or different tumors on the same patient (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1 ). The result was similar to the previous reports in which RBM10 was found with a high mutation rate (16%) in radiological subsolid nodules 25 , and a high mutation rate (21%) in preinvasive and early-stage lung adenocarcinomas 26 . In addition, several oncogenes (such as EGFR , SPTA , and RB1 ) had different mutations in the same or different tumors on the same patient (Fig.…”
Section: Resultssupporting
confidence: 92%
“…It is generally accepted that multiple GGNs in patients come out from different lineages, meaning that hematogenous metastasis do not happen to GGNs 5 , 30 , 31 , 33 . However, the possibility that a small number of GGNs come from the same ancestor cannot be excluded, which can be explained by the air space theory 25 , 34 36 . In our cohort, the definite IM case (a pGGN and a solid nodule) shared multiple mutations, providing evidence that a small portion of GGNs might be the result of early metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Much effort has been devoted to decoding the indolent nature of SSN. Our team has found that the genome of SSN has a relatively low mutation burden and few copy number alterations (11). The tumor lesion is a complex ecosystem composed of malignant cells, various types of immune cells, and stromal cells (12).…”
Section: Introductionmentioning
confidence: 99%
“…20 Histologically, solid components of SSNs were usually related to histologic subtypes like papillary, acinar, solid, or invasive mucinous adenocarcinoma. 3 Radiogenomically, Li et al 28 found that higher ratios of solid components in SSNs were accompanied by significantly higher mutation frequencies in EGFR, TP53, RBM10, and ARID1B, suggesting that these genes play roles in the progression of lung adenocarcinomas. Anyway, proper management of SSNs is critical.…”
Section: Discussionmentioning
confidence: 99%